Green preparation of methyl cinnamate and evaluation of its antifungal activity as a potential wood preservative - Haug, Elizabeth; Ruiz, Diego; Raffaeli, Natalia; Saparrat, Mario; Romanelli, Gustavo (Universidad Pedagógica y Tecnológica de Colombia, 2019)
Wood constitutes a material susceptible to fungal degradation, presenting frequent and aggressive deterioration when it is put into service. Although over the years compounds have been developed for their protection with various methods of impregnation, many of them present strong environmental questions. The present work focuses on obtaining a preservative with potential antifungal activity for wood through a procedure of low environmental impact. The synthesis of methyl cinnamate (CiM) from cinnamic acid and methanol was carried out by catalysis with acids of Preyssler structure, with a yield of 49% and a selectivity of 100%. Subsequently, the antifungal action of the compound against Gloeophyllum sepiarium (Wulf.: Fr.) P. Karst, fungus causing brown rot was evaluated in-vitro. To do this, the growth of the fungus was comparatively analyzed on a control agarized culture medium and in the presence of CiM. The CiM demonstrated antifungal effect from 2000 ppm, though it was dependent on the incubation temperature. Further research is needed on wood to confirm its potential as a green preservative.